Examining the Social Construction of Highly Educated Women - Lasmery RM Girsang; Miletresia Miletresia (Ikatan Sarjana Komunikasi Indonesia, 2024)
This study discusses the realities faced by single female workers in urban areas who are still bound by stereotypes. It is undeniable that women remain a significant topic of discussion as there are several views that hinder women, particularly in pursuing their achievements in higher education. This article focuses on how women strive to overcome stereotypical views that limit their rights. Examine the increasingly widespread stereotypes that raise society’s awareness on emerging gender-based generalizations. Thus, through recognizing gender roles, women shape their identities by constructing their own realities. Therefore, by applying an exploratory-qualitative approach, the authors found three informants in Jakarta who are challenging societal constructions. Based on the Social Construction Theory, this study shows that even though women have formal education and high jobs, they still face questions from their environment that influence their identity construction.